POTENSI EKONOMI KABUPATEN MINAHASA SELATAN - Feybi ., Hadjarati; Juliana R. Mandei; Ribka M. Kumaat (Sam Ratulangi University, 2016)
The problem in this research is the in the basic sector in South Minahasa District and the potential sectors to be developed as a support for economic growth in South Minahasa District. The purpose of this study is to analyze the basic sector and potential sectors in South Minahasa district. The study lasted four months starting June 2016 until September 2016, started with the preparation period to the preparation of research studies. This study used secondary data obtained from the Central Bureau of Statistics of North Sulawesi province and the Central Bureau of Statistics South Minahasa district. Analysis used LQ, Shift Share, and MRP. The Result shows that the base sector in the Domestic Regional Product Of South Minahasa District. There are four sectors Agriculture sector, Mining and Quarrying, Manufacturing Industry Sector, and the Construction Sector. Values shift share South Minahasa district likely to lead to an economy that will grow relatively slowly and did not have a competitive advantage, and There are two sectors of the value of MRP that stand out in North Sulawesi province and South Minahasa District the Construction Sector, and Health Services and Social Activity sectors. Manufacturing sector, and Administration Sector, Government, Defense and Compulsory Social Assurance. These sectors are expected to be a potential role in contributing to the growth in north Sulawesi province because These sectors are potential sector that can be developed in South Minahasa district.